Psychological Problem of the Main Character in James Bird’s the Brave (International Journal of Education and Literature, 2025)
The title of this research is Psychological Problem of the Main Character in James Bird's The Brave. This study aims to determine the psychological problems faced by the main character, the causal factors that contribute to the main character, and what effects of the psychological issues toward the family relationships and social life of the main character. This data was collected by reading the novel repeatedly and then using the note-taking technique to find statements related to the topic to be analysed. The main and supporting theories that are applied in writing this research are taken from Stanley Rachman and Padmal de Silva in their book entitled Obsessive-Compulsive Disorder (2009).. Based on the results of the analysis, the psychological problems of the main character are found to be Obsessive-Compulsive Disorder from childhood. Obsessive-Compulsive Disorder affects him and the environment by blaming himself, making his anxiety recur, and making his brain panic and traumatized. In addition, the effect of Obsessive-Compulsive Disorder on those around him is that he makes people frustrated and annoyed when talking to him, and he loses hisfriends..